Prequestionamento e questões de ordem pública no recurso extraordinário e no recurso especial - Mangone, Kátia Aparecida (2010)
The present work examines the prequestionamento and, principally, analyses if matters of public order could be known in the judgement of Extraordinary Appeals to the Supreme Court and Special Appeals to the Superior Court of Justice. Firstly, it is studied the Constitutional Model of these Extraordinary and Special Appeals, talking about the history of the High Courts and how these appeals came out and were defined by the Brazilian Federal Constitutions. The general theory of the Extraordinary Appeals is analysed with its requirements of admissibility. The devolutive and transferable effects are studied to show that Extraordinary and Special Appeals do not have the last one. The idea of the complete motivation of the decision is an important topic of the work. The appeal of requesting clarification of a decision is studied in this context. The preclusion, definition and examples of matters of public order are examined too. It was possible, after this work, to verify that the constitutional rules must be observed and they determine that it must exist decided cause about the issue at the appealed decision. The knowledge of matters of public order by the High Courts depends on it, because the Constitution does not make exceptions. The function and the purpose of the Supreme Court and the Superior Court of Justice, the objectives of the Extraordinary Appeal and the Special Appeal, their requirements and the importance of the uniform interpretation of the Federal Constitution and the Federal Laws are topics to which special focus was given